2018
DOI: 10.1097/ta.0000000000001607
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Critical Care Air Transport Team (CCATT) ventilator management on combat mortality

Abstract: Therapeutic/care management, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The study demonstrated an association between guideline compliance and decreased ventilator days, intensive care unit days, and 30-day mortality. 34 Studies investigating needle decompression reported 76% failure (potentially correlated with chest wall thickness) with 39% performed in patients without pneumothorax. 33 Overall, studies investigating prehospital thoracostomy reported a 5.2% to 27% increase in complications such as empyema, lung contusions, and pneumonia.…”
Section: Resultsmentioning
confidence: 99%
“…The study demonstrated an association between guideline compliance and decreased ventilator days, intensive care unit days, and 30-day mortality. 34 Studies investigating needle decompression reported 76% failure (potentially correlated with chest wall thickness) with 39% performed in patients without pneumothorax. 33 Overall, studies investigating prehospital thoracostomy reported a 5.2% to 27% increase in complications such as empyema, lung contusions, and pneumonia.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2,177 study subjects were associated with the included articles. There were two Level I systematic reviews, 4,5 33 Level II prospective studies with 647 subjects, seven Level III retrospective studies with 1,455 subjects, [39][40][41][42][43][44][45] and two Level IV case series with four subjects. 46,47 There were two Level V case reports 48,49 and 63 pertinent review articles.…”
Section: Resultsmentioning
confidence: 99%
“…57 Several studies from the United States military evacuation of casualties from the conflicts in Iraq and Afghanistan provide some insight into adverse events. 58,59 These trials included mechanically ventilated subjects in cases of non-battle injuries (20%) and battle injuries (60%). In the latter group, subjects were frequently ventilated at settings that did not comply with the ARDSNet tidal volume and PEEP/F IO2 tables.…”
Section: Adverse Events During Interhospital Transportmentioning
confidence: 99%